Growth of Large‐Sized 2D Ultrathin SnSe Crystals with In‐Plane Ferroelectricity. (14th February 2023) - Chiu, Ming‐Hui; Ji, Xiang; Zhang, Tianyi; Mao, Nannan; Luo, Yue; Shi, Chuqiao; Zheng, Xudong; Liu, Hongwei; Han, Yimo; Wilson, William L.; Luo, Zhengtang; Tung, Vincent; et al.
Abstract: Tin (II) selenide (SnSe) is an emerging 2D material with many intriguing properties, such as record‐high thermoelectric figure of merit (ZT), purely in‐plane ferroelectricity, and excellent nonlinear optical properties. To explore these functional properties and related applications, a crucial step is to develop controllable routes to synthesize large‐area, ultrathin, and high‐quality SnSe crystals. Physical vapor deposition (PVD) constitutes a reliable method to synthesize 2D SnSe, however, effects of various growth parameters have not yet been systematically investigated, and current PVD‐synthesized flakes are often thick (>10 nm) with small lateral sizes (<10 µm). In this work, high‐quality 2D SnSe crystals are synthesized via low‐pressure PVD, which display in‐plane ferroelectric domains observed by piezoresponse force microscopy and polarization‐dependent reflection spectroscopy. Detailed studies regarding the roles of various parameters are further carried out, including substrate pre‐annealing, growth duration, temperature, and pressure, which enable to rationally optimize the growth and obtain 2D SnSe crystals with lateral sizes up to ≈23.0 µm and thicknesses down to ≈2.0 nm (3–4 layers). This work paves the way for the controlled growth of large‐area 2D SnSe, facilitating the future exploration of many interesting multiferroic properties and applications with atomic thickness. Abstract : High‐quality 2D ferroelectric SnSe is synthesized by low‐pressure physical vapor deposition. To achieve large‐sized ultrathin SnSe, effects of substrate pre‐annealing, growth duration, temperature, and pressure are studied in detail. Rationally optimized conditions yield SnSe crystals with lateral sizes up to 23.0 µm and thicknesses of 5.0 nm, while smaller flakes can have thicknesses down to 2.0 nm.